1983
DOI: 10.1111/j.1476-5381.1983.tb10546.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that 5‐hydroxytryptamine in the forebrain is involved in naloxone‐precipitated jumping in morphine‐dependent rats

Abstract: 1 A withdrawal syndrome was precipitated by naloxone in morphine-dependent rats injected with 5,7-dihydroxytryptamine (5,7-DHT) in the ventromedial tegmentum (VMT) at the level of the nucleus interpeduncularis. 2 5,7-DHT, which markedly depleted 5-hydroxytryptamine (5-HT) in the forebrain but not in the brainstem, significantly reduced jumping in abstinent rats with no significant effect on other withdrawal signs.3 The effect of morphine 10mg kg-lon responses on the hot plate was unchanged in 5,7-DHTtreated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, the behavior of recombinant mice lacking 5-HT and dopamine reuptake transporters or 5-HT 1B receptors suggests that 5-HT interacts with dopamine in the NAcc to influence drug self-administration (Rocha et al, 1998;Uhl et al, 2002). Both the reinforcing property of morphine and withdrawal syndrome are affected by 5-HT receptor ligands, supporting the hypothesis that 5-HT plays a role in opiate addiction (Cervo et al, 1983;Carboni et al, 1989;Harris and Aston-Jones, 2001). …”
mentioning
confidence: 64%
“…Moreover, the behavior of recombinant mice lacking 5-HT and dopamine reuptake transporters or 5-HT 1B receptors suggests that 5-HT interacts with dopamine in the NAcc to influence drug self-administration (Rocha et al, 1998;Uhl et al, 2002). Both the reinforcing property of morphine and withdrawal syndrome are affected by 5-HT receptor ligands, supporting the hypothesis that 5-HT plays a role in opiate addiction (Cervo et al, 1983;Carboni et al, 1989;Harris and Aston-Jones, 2001). …”
mentioning
confidence: 64%
“…In addition, double dopamine/5-HT transporter knockout mice fail to show cocaine CPP (Sora et al 2001), indicating a role for 5-HT as well as dopamine in psychostimulant reward. The 5-HT system has also been shown to be involved in both euphoric effects of opioids (Carboni et al 1989; Carboni et al 1988; Carboni et al 1989; Glick and Cox, 1977; Alaei et al 2002) and the dysphoric responses that are part of the withdrawal syndrome (Cervo et al 1983; Harris and Aston-Jones, 2001; Goeldner et al 2011; Cervo et al 1981). There is also a high degree of comorbidity of affective disorders such as major depression with opiate dependence (Brooner et al 1997; Mason et al 1998; Pani et al 1997; Rounsaville et al 1982; Woody et al 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 5-HT has been hypothesized to be one of the factors involved in the changes in physiology and behavioral state which occur during opiate withdrawal. However, several findings have suggested that 5-HT is not responsible for the physical symptoms of withdrawal (Blasig et al, 1976;Silverstone et al, 1993), except for a possible role in jumping behavior (Cervo et al, 1983;Way et al, 1968). For example, it has been shown that serotonergic transmission blockade, either by specific 5-HT lesion (Ho et al, 1972) or a 5-HT antagonist (Cervo et al, 1981;Samanin et al, 1980) along with chronic morphine treatment, reduces the development of jumping behavior during morphine withdrawal.…”
Section: Introductionmentioning
confidence: 99%